Integrated Strategy to Curtail Illegal Gold Mining: A Case Study in Central Kalimantan, Indonesia - Hasibuan, Ongku Parmonangan; Tjakraatmadja, Jann Hidajat; Sunitiyoso, Yos (School of Business and Management Institut Teknologi Bandung, 2021)
Abstract. Illegal gold mining has disturbed the operation of a mining company (Indo Muro Kencana) in Central Kalimantan since the early 1990s. Several disputes have happened, including two serious conflicts, causing financial losses, damage to facilities, and fatalities, forcing the company to stop operations in 2002 and 2013. Eventually, the original investors abandoned the site. Various countermeasures were taken, including harsh law enforcement involving police and military forcesâ€™ deployment, yet the illegal mining activities continued. Since 2015, the new management has implemented new approaches; within five years, the number of illegal miners has decreased considerably. This study aims to identify the reasons behind the disputes and how the new management reduces illegal mining within its concession without triggering further conflict. This research is a case study using in-depth interviews, complemented by a study of corporate and media documents. Five factors were identified behind the previous conflicts. The new managementâ€™s integrated strategy to manage social issues, including illegal mining, started with social mapping, then an integrated team to deal with social issues was established, and finally, an integrated plan was introduced with four agendas: engagement, presence, respect and inclusiveness, and cohesiveness. This study contributes to company-community model building in similar circumstances and, in practice, offers a solution to curtail illegal gold mining, particularly in Indonesia.Â Keywords: Conflict, illegal gold mining, illegal miners, integrated, Kalimantan.